Case report: Chronic Candida albicans meningitis: a rare entity diagnosed by metagenomic next-generation sequencing - Kuenzli, Andrea B.; Müller, Mandy D.; Z`Graggen, Werner J.; Walti, Laura N.; Martin, Yonas; Lazarevic, Vladimir; Schrenzel, Jacques; Oberli, Alexander (Frontiers in Cellular and Infection Microbiology, 2024)
The aetiology of chronic aseptic meningitis is difficult to establish. Candida meningitis in particular is often diagnosed late, as cerebrospinal fluid (CSF) work-up and imaging findings are nonspecific. A 35-year-old patient with chronic aseptic meningitis, for which repeated microbiological testing of CSF was unrevealing, was finally diagnosed with Candida albicans (C. albicans) meningitis with cauda equina involvement using metagenomic next-generation sequencing (mNGS). This report highlights the diagnostic challenges and the difficulties of treating shunt-associated fungal meningitis.